COVID-19 and the Disinheritance of an Ableist World - Johnathan Flowers (International Journal of Critical Diversity Studies, 2021)
This paper will resituate the presumed accessibility gains that have emerged in the wake of COVID-19 not as gains for disabled people, but rather as the products of a world that is prepared for some people and some bodies and not for other people and other bodies. I will show that a more productive approach to understanding the sudden possibility of impossible accommodations would be accomplished by drawing upon Sara Ahmed's treatment of the inheritance of a world, inheritance that places some objects within one's reach while denying one access to other objects. On this view, ableism, as an organizing force in the world, serves to determine what bodies can and cannot do by virtue of the way that it “prepares” the world for some bodies and not for other bodies. As I will argue, the previous impossibility of the current widespread accommodations in academia and society broadly was due to the inheritance of an ableist world. designed to be inherited by some people and their bodies and not by other people and their bodies.